An Algorithmic Approach to the Surgical Treatment of Chronic Ischemia of the Hand: A Systematic Review of the Literature. Issue 5 (May 2016) - Thibaudeau, Stephanie; Serebrakian, Arman T.; Gerety, Patrick A.; Levin, L. Scott
Abstract : Background: Chronic ischemia of the hand can lead to intractable pain, cold intolerance, and digital necrosis, affecting up to 4.8 percent of patients undergoing vascular surgery. Treatment of patients suffering from chronic hand ischemia, in particular, the subset of patients with a nonreconstructible distal arterial tree, can be a significant challenge for hand surgeons. The purpose of this systematic review is to analyze the outcomes of surgical therapies in an effort to define the efficacy of each intervention. The authors also revisit the treatment algorithm for nontraumatic chronic hand ischemia. Methods: A systematic search of the literature published since 1990 in the PubMed/MEDLINE database was performed using keywords. Articles were eligible if they described clinical studies of human patients with nontraumatic chronic hand ischemia who underwent sympathectomy, arterial bypass, or venous arterialization. Pain improvement, wound healing, and new ulcerations were primary outcome measures. Primary patency rates and limb salvage data were also collected as primary outcome measures in the bypass and arterialization study arms. Results: For sympathectomy, arterial bypass, and venous arterialization, pain relief was achieved in 89, 100, and 100 percent of patients, respectively; whereas wound healing occurred in 74, 93, and 75 percent, respectively. Postoperative ulcerations were 0, 3, and 8 percent, respectively. No secondary amputations were reported in these 33 studies. Complication rates were moderately high (2.1 to 30.8 percent). Conclusion: This systematic review confirms that sympathectomy, arterial bypass, and venous arterialization are efficacious treatments, and allows for an algorithmic approach to the surgical treatment of chronic hand ischemia. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.